Variability of Sugars Concentrations in Infant Follow-on Formulas with Higher Consumption in Peru: A Preliminary Study - Munives-Marcos, Angélica K. (2023)
Aim: The aim of the present preliminary study was to determine sugar concentration in infant follow-on formulas most widely consumed in Peru. Materials and methods: In this descriptive and observational study, the sample was represented by five brands of infant follow-on formulas most consumed in Peru (A, Similac 2; B, Enfamil 2®; C, NAN 2®; D, Baby Lac Pro 2®; and E, Lacti Kids Premium 2®); with two samples of each, collected at two different locations in the Peruvian capital. Subsequently, the concentration of total and individual sugars (lactose, sucrose, glucose, fructose, and maltose) was determined using the high-performance liquid chromatography (HPLC) method in a specialized laboratory. For the comparison of means, Welch’s robust analysis of variance (ANOVA) test for equality of means and Tukey’s post hoc test were used. The significance level was p < 0.05. Results: The total sugars concentration per 100 gm of the five infant follow-on formulas showed a mean of 38.9 ± 11.03 gm, being Similac 2, the infant follow-on formula, with the highest concentration of 50.33 ± 0.11 gm and Enfamil 2, the lowest with 22.75 ± 0.06 gm. The average sugars recorded in the laboratory were compared with those on the product label for Similac 2 (50.3 and 53.1 gr), NAN 2 (46.5 and 51.5 gr), Baby Lac Pro 2 (41.5 and 57.0 gr), Lacti Kids Premium 2 (33.3 and 57.0 gr) and Enfamil 2 (22.8 and 56.0 gr). Furthermore, when comparing the infant follow-on formulas, significant differences were observed between all sugar concentrations (p < 0.001), with the follow-on formula with the significantly higher sugar concentration being Similac 2 (p < 0.001) and the one with the significantly lower concentration being Enfamil 2 (p < 0.001). Regarding individual sugars, per 100 gm analyzed, fructose and maltose registered values